COMPLEX BREAST CYSTS: SONOGRAPHIC FINDINGS AND HISTOPATHOLOGIC RESULTS - Füsun Taşkın; Kutsi Köseoğlu; Serdar Özbaş; Muhan Erkuş; Can Karaman (European Journal of Breast Health, 2010)

(untitled)
Purpose: To evaluate the sonographic findings and histopathological diagnosis of complex breast cysts, and to assess the diagnostic reliability of a 14G core-needle biopsy.Patients and Methods: Sixty-one complex breast cysts that underwent a 14 G core-needle biopsy and/or surgical excisions were retrospectively analyzed. Cystic masses with thick wall- thick septation and with solid component were included. Mixed lesions with both cystic and solid appearance were excluded. Radiologic findings and histopathologic diagnosis of these lesions reviewed retrospectively.Results: Of 61 lesions, 39 (64%) were complex cysts with thick wall and/or thick septation and 22 (36%) were complex cysts with solid component. Forty- eight (79%) lesions were diagnosed as benign and 13 (21%) lesions were diagnosed as malignant. Of the 39 complex cysts with thick wall-thick septation, 31 (79%) lesions were diagnosed as benign and 8 (21%) lesions were malignant. Of the 22 complex cysts with solid component, 17 (77%) lesions were diagnosed as benign and 5 (23%) were malignant.Conclusion: Complex breast cysts have malignancy risk and usually require biopsy. Thirteen of 61 (21%) complex cysts proved malignant in our study. Core needle biopsy is a safe and reliable diagnostic procedure in the management of these cases. However, in cases of clinical/radiological/pathological discordance or the presence of atypical cells, a surgical excision should be performed.